Digital Transformation and Environmental Sustainability: The Journey of Batik and Ecoprint Entrepreneurs Facing Global Creative Industry Challenges (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This research aims to analyze how digital transformation and environmental sustainability strategies are implemented by batik and ecoprint entrepreneurs facing global creative industry challenges. Employing a descriptive qualitative method, data was collected through in-depth interviews, direct observation, and document analysis involving key local entrepreneurs. The findings demonstrate that digitalization—especially via social media marketing and digital branding—significantly broadens market access and enhances the environmental image of products. Internally, digital training and SOP documentation strengthen knowledge management and innovation capabilities. Moreover, entrepreneurs adopt green innovation and circular economy principles, such as water and energy reduction, utilization of natural dyes, and integrated waste management through waste banks. Community engagement in environmental awareness and skill-building proves critical for reinforcing social and ecological values alongside economic gains.
Keywords: digital transformation; environmental sustainability; green innovation; circular economy; creative industry